The effectiveness of service learning-esd content in equipping students with problem-solving skills - Nurhaliza, Nurhaliza; Rustaman, Nuryani; Purwianingsih, Widi; Salahuddin, Salahuddin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Service learning contains ESD is one of the learning approaches that is suitable for students in the field of science. This research aims to measure the level of students' problem-solving skills. The method used in this study is a quasi-experimental experiment or Quasi Experimental Design, the experimental design used is one group pre-test-post test. The instrument used in this study is in the form of a test consisting of 15 description questions according to five aspects of problem-solving skills. The instruments were given to students in the experimental class and the control class. The results showed that there was a significant influence on the problem-solving skills of students in the experimental class with the medium N-gain category. It can be concluded that through service learning contains ESD, students have better problem-solving skills.